La Ilustración y uno de sus genuinos productos: La Real Sociedad Bascongada de los Amigos del País - Zabaleta Arrieta, Aitor (Boletín de la Real Sociedad Bascongada de Amigos del País, 2013)
The 18th century ushers in and prepares for the arrival of the contemporary world. It is a fundamental period in the history of the West. During the Enlightenment we pass from a feudal structure to a bourgeois regime and the Age of Enlightenment is the ideological projection between both societies, a new way of thinking which causes profound changes in Europe. This work concentrates on a genuine creation of the Enlightenment, the Royal Society of Friends of the Basque Country, true precursor of the Enlightenment and fi rst economic society. The aim is to understand the role the Society played in the world of ideas and art, in particular in the introduction and consolidation of the artistic movement typical of the time.